ANALISIS PENGETAHUAN MAHASISWA TERHADAP GIZI DAN DIET: analysis of student knowledge of nutrition and diet - Zanjabiela , Aisyatu Khoirunnisa; Lestari, Amanda Putri; Alpazri, Bukhori; Saputra, Marcelino Herdian; Lestari, Silvi Rahmasari; Fauzia, Stefani Putri; Nurjanah, Suci (Jurnal Keperawatan Sumba (JKS), 2024)
Behaviors related to lifestyle and health of adults, including adolescents and children, are partly related to adult health problems. The aim of this study was to obtain an overview of nutrition among Indramayu State Polytechnic students and identify nutrition-related knowledge factors. To achieve these objectives, questionnaires were distributed to 30 students of Indramayu State Polytechnic. This study will try to explore how and how much understanding they have about nutrition, this study uses questionnaires that are given directly to students to identify their identity and their dietary patterns. This research is also descriptive and produces data in the form of numbers. This data was analyzed using the program. The knowledge of the respondents showed that the average respondent who had moderate knowledge (15 respondents or 50%) to poor knowledge (4 respondents or 13.4%), namely 19 out of 30 students had a frequency value of poor (63.4%). This shows that respondents have less knowledge on Nutrition and Diet. It is recommended for students to further improve their understanding of nutrition and diet by expanding their knowledge about the development of nutrition and diet in Indonesia.